Titration of the gap junction protein Connexin43 reduces atherogenesis - Morel, Sandrine; Chanson, Marc; Nguyen, Thien D.; Glass, Aaron M.; Sarieddine, Maya Z. Richani; Meens, Merlijn J.; Burnier, Laurent; Kwak, Brenda R.; Taffet, Steven M. (Thrombosis and Haemostasis, 2014)
Ubiquitous reduction of the gap junction protein Connexin43 (Cx43) in mice provides beneficial effects on progression and composition of atherosclerotic lesions. Cx43 is expressed in multiple atheroma-associated cells but its function in each cell type is not known. To examine specifically the role of Cx43 in immune cells, we have lethally irradiated low-density lipoprotein receptor-deficient mice and reconstituted with Cx43+/+, Cx43+/− or Cx43−/− haematopoietic fetal liver cells. Progression of atherosclerosis was significantly lower in aortic roots of Cx43+/− chimeras compared with Cx43+/+ and Cx43−/− chimeras, and their plaques contained significantly less neutrophils. The relative proportion of circulating leukocytes was similar between the three groups. Interestingly, the chemoattraction of neutrophils, which did not express Cx43, was reduced in response to supernatant secreted by Cx43+/− macrophages in comparison with the ones of Cx43+/+ and Cx43−/− macrophages. Cx43+/− macrophages did not differ from Cx43+/+ and Cx43−/− macrophages in terms of M1/M2 polarisation but show modified gene expression for a variety chemokines and complement components. In conclusion, titration of Cx43 expression in bone marrow-derived macrophages reduces atherosclerotic plaque formation and chemoattraction of neutrophils to the lesions.
Keywords: Atherosclerosis; Connexin43; neutrophils; macrophages